PEREMPUAN DAN SEKS : STUDI HADIS-HADIS TENTANG LAKNAT MALAIKAT TERHADAP ISTRI YANG MENOLAK AJAKAN SUAMI - Isti'anah, Isti'anah (IAINU Kebumen Prodi IAT, 2022)
In married life, the husband should be able to position his wife as a balanced and equal partner. Not only as a complement to life and sexual satisfaction alone. A husband has the responsibility to help his wife's work, and vice versa, the wife must take part in helping to bear the burden of responsibility to relieve her husband. Husbands may not claim the right of